RIFIZOSTREP – NEW DRUG AGAINST TUBERCULOSIS - G.Kh , Mamadullaev; U.M, Fayziev (PT. Antis International Publisher, 2024)
The article presents the results of bacteriological studies of the internal organs of guinea pigs and rabbits experimentally infected with M. bovis and M. tuberculosis with the subsequent use of a new anti-tuberculosis drug “Rifisostrep”.